2019
DOI: 10.1093/ajcn/nqy356
|View full text |Cite|
|
Sign up to set email alerts
|

Using metabolic profiling and gene expression analyses to explore molecular effects of replacing saturated fat with polyunsaturated fat—a randomized controlled dietary intervention study

Abstract: Background Replacing dietary saturated fatty acids (SFAs) with polyunsaturated fatty acids (PUFA) reduces the plasma low-density lipoprotein (LDL) cholesterol and subsequently the risk of cardiovascular disease. However, beyond changes in LDL cholesterol, we lack a complete understanding of the physiologic alterations that occur when improving dietary fat quality. Objectives The aim of this study was to gain knowledge of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 58 publications
(48 reference statements)
1
35
1
Order By: Relevance
“…None of the gene transcripts encoding proteins related to lipid metabolism were changed by the ND compared to the CD. We have previously shown that exchanging SFA with PUFA reduced total cholesterol and LDL-C by 9% and 11%, respectively, among subjects with slightly elevated cholesterol [29], and changed the PBMC expression levels of several lipid metabolism-related genes [30]. The reason why we did not observe any changes in lipid metabolism-related genes in the present study, may be due to the smaller effect of the ND on the lipid profile as previously shown [16].…”
Section: Discussioncontrasting
confidence: 45%
“…None of the gene transcripts encoding proteins related to lipid metabolism were changed by the ND compared to the CD. We have previously shown that exchanging SFA with PUFA reduced total cholesterol and LDL-C by 9% and 11%, respectively, among subjects with slightly elevated cholesterol [29], and changed the PBMC expression levels of several lipid metabolism-related genes [30]. The reason why we did not observe any changes in lipid metabolism-related genes in the present study, may be due to the smaller effect of the ND on the lipid profile as previously shown [16].…”
Section: Discussioncontrasting
confidence: 45%
“…Assessing the bidirectional relationship between diet and the immune system can be undertaken utilizing multiple approaches. In human intervention studies, investigators have assessed the impact of bioenergetic status [1], isolated nutrients [2][3][4][5][6], and dietary patterns, such as the Mediterranean Diet [7,8], in both controlled feeding and free-living intervention studies on numerous indices of immune function (e.g., circulating cytokines, high-sensitivity C-reactive Protein, antibodies, tissue-specific…”
Section: Approaches To Studying Nutrition and The Immune Systemmentioning
confidence: 99%
“…See Supplemental Methods for detailed description of PBMC isolation, RNA extraction, microarray analysis and gene expression pre-processing steps. Briefly, we collected PBMCs and extracted RNA according to standardized protocols [6]. The subsequent microarray gene expression analyses were performed using HumanHT-12 Expression BeadChips (Illumina Inc., CA, USA), and followed standard Illumina protocol (Illumina Inc., CA, USA).…”
Section: Pbmc Gene Expression Analysis Pipelinementioning
confidence: 99%